PENGARUH LABA USAHA, KREDIT MIKRO DAN LITERASI KEUANGAN TERHADAP KESEJAHTERAAN EKONOMI RUMAH TANGGA UMK DI INDONESIA - Khaira, Sajida; Yanuarta RE, Ramel (Financial Management Studies, 2024)
This study aims to examine the effect of business profit, microcredit, financial literacy (ownership of savings accounts, and knowledge of financial institutions that provide loans) on the economic welfare of MSE households in Indonesia, using IFLS data wave 5 in 2014 and multiple regression analysis using Stata software. The results of the study revealed that business profit significantly improves the economic welfare of MSEs, while microcredit has no significant effect. Meanwhile, financial literacy as measured by ownership of savings accounts and knowledge of financial institutions that provide loans also has a significant effect. This study emphasizes the importance of effective strategies in utilizing business profit, microcredit and financial literacy to improve the economic welfare of MSE households in Indonesia